The Civil War in Libya and Its Impact on National Identity (قضايا سياسية, 2024)
To a large extent, civil wars lead to the disintegration and fall of states, or weaken them into fragile and failed states, and then the role of the state and its institutions capable of facing crises in the long and short term is absent. Internal disputes - especially tribal and regional, and rampant corruption in the country - contribute significantly to the outbreak of civil war when some feel that they have become one of the oppressed groups within the state, and this reflects a bitter and ill-considered reality whose consequences are often dire. The absence of effective government institutions from the truth and work to restore relations between the people and the ruling authority and not leave a large gap that may be exploited in one way or another to fuel the civil war to reach the goals that the ruling authority believes are important at all levels.